The Determinants of Performance in the Nigerian Banking Industry 2004-2014 - Adefunke, Bajomo Olubunmi; Enisan, Akinlo Anthony (Asian Journal of Economic Modelling, 2019)
The Nigerian government strategy to alter the structure and scope of its banking sector via consolidation and other accompanying sectorial reforms did not only impact the soundness of banks with significant cost of state sponsored interventions, policy also had long run implications for nature of industry competition and performance with direct consequence for the determinants of the industry’s performance. Observed alterations to structure of the banking sector structure post these interventions directly impacted borrowing costs and motivations for the resulting enlarged financial institutions to extend credit to the real sector. Banks with improved performance post reforms have enhanced capacity to absorb adverse volatility in the system, hence, imperatives of evaluating the determinants of the industry’s performance. The study analyzes determinants of performance in the Nigerian financial industry in pre and post consolidation era (2004-2014) using panel data with fixed-cross sectional effect to determining bank specific- industry and macro determinants of performance. Derived results show bank specific factors such as ability to manage expenses, capital, and intensity of loan usage significantly affect banks profitability. Model estimated from the study, however, strongly rejected the structure-conduct-performance (SCP) hypothesis as the influence of intense concentration in banking though highly significant is negative, which implies that banks are unable to engage in non-competitive behavior as the Nigerian banking space is competitive and highly regulated. In addition, impacts of most macroeconomic factors are found to be negligible. However, exchange rate variation affects bank’s profitability in a significant manner.